2019
DOI: 10.1016/j.mtphys.2019.100169
|View full text |Cite
|
Sign up to set email alerts
|

Boron isotope effect on the thermal conductivity of boron arsenide single crystals

Abstract: Boron arsenide (BAs) with a zinc blende structure has recently been discovered to exhibit unusual and ultrahigh thermal conductivity (k), providing a new outlook for research on BAs and other high thermal conductivity materials. Technology for BAs crystal growth has been continuously improving, however, the influence of boron isotopes, pure or mixed, on the thermal conductivity in BAs is still not completely clear. Here we report detailed studies on the growth of single crystals of BAs with different isotopic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…It has been found that laser excitations can produce Raman scattering from electronic excitations, which is called electronic Raman scattering (ERS). ERS produces a scattering background and a Fano line shape of Raman peaks, which have been found in previous Raman studies on BAs. , Moreover, ERS enables observation of the correlation between hole concentration and κ in BAs . A similar correlation has been established for our samples, as shown in Figure b.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It has been found that laser excitations can produce Raman scattering from electronic excitations, which is called electronic Raman scattering (ERS). ERS produces a scattering background and a Fano line shape of Raman peaks, which have been found in previous Raman studies on BAs. , Moreover, ERS enables observation of the correlation between hole concentration and κ in BAs . A similar correlation has been established for our samples, as shown in Figure b.…”
Section: Resultssupporting
confidence: 84%
“…ERS produces a scattering background and a Fano line shape of Raman peaks, which have been found in previous Raman studies on BAs. 8,38 Moreover, ERS enables observation of the correlation between hole concentration and κ in BAs. 8 A similar correlation has been established for our samples, as shown in Figure 3b.…”
Section: Resultsmentioning
confidence: 99%
“…Samples made of different boron sources had different characteristic Raman peaks. [ 50 ] X‐ray diffraction and Raman scattering data on our samples in Figure S1, Supporting Information, were included.…”
Section: Methodsmentioning
confidence: 99%
“…Further details about the synthesis can be found in Refs. [49,50] The authors used various boron sources in the synthesis processes. Sample A (≈1100 W m −1 K −1 ) was grown with 10 B isotopes, Sample B (≈600 W m −1 K −1 ) was grown with nat B particles (19.9% 10 B and 80.1% 11 B), and Sample C (≈350 W m −1 K −1 ) was grown with 11 B isotopes.…”
Section: Methodsmentioning
confidence: 99%
“…Engineering of phonon topology is one of the main strategies to manipulate thermal properties through phonon engineering besides doping [22], creating solid solution [23], isotopic engineering [24,25] and nanostructuring [26,27] Many novel properties, such as low thermal conductivity [28][29][30], negative thermal expansion [31], and anomalous phase transitions [32], can be attributed to exotic phonon dispersion topology, e.g., crossing/anticrossing behaviors [28,29] bunched acoustic phonon, and dispersion waterfall [33]. Recently, local phonon dispersion nesting behaviors have been shown to augment acoustic-optical three-phonon scattering channels, amplify anharmonicity, and suppress lattice thermal transport [34,35].…”
mentioning
confidence: 99%